Multiple periodic solutions for a class of second-order nonlinear neutral delay equations (Abstract and Applied Analysis)
By means of a variational structure and Z 2 -group index theory, we obtain multiple periodic solutions to a class of second-order nonlinear neutral delay equations of the form0, au>0$"> x ″ ( t − τ ) + λ ( t ) f ( t , x ( t ) , x ( t − τ ) , x ( t − 2 τ ) ) = x ( t ) , λ ( t ) > 0 , τ > 0 .